PENGARUH RETURN ON ASSETS DAN NET PROFIT MARGIN TERHADAP HARGA SAHAM PADA PERUSAHAAN PERTAMBANGAN SUB SEKTOR MINYAK DAN GAS YANG TERDAFTAR PADA BURSA EFEK INDONESIA PERIODE 2012-2017 - Lestari, - Fani (EKONOMIA, 2019)
Fani Lestari, 2018. Faculty of Economics, University August 17, 1945 Samarinda. Effect of return on assets and net profit margin on the stock price of oil and gas sub-sector mining companies listed on the Indonesia Stock Exchange for the 2012-2017 period. Under the guidance of Mrs. Titin Ruliana as counselor I and Mrs. Beatrix Tandirerung as counselor II. This study aims to determine the effect of return on assets and net profit margins on stock prices in oil and gas sub-sector mining companies listed on the Indonesia stock exchange for the 2012, 2013, 2014, 2015, 2016 and 2017 periods. The theory of this research is financial management which focuses on the effect of profitability ratios using two (variables) namely return on assets and net profit margin. The analytical tool used is return on assets and net profit margin, and uses multiple linear regression analysis. The data needed are financial statements 2012, 2013, 2014, 2015, 2016, 2017. The results showed 1) Return on assets did not have a significant effect on stock prices on oil and gas sub-sector mining companies listed on the Indonesian stock exchange for the period 2012-2017, the hypothesis was rejected, 2) Net profit margins did not have a significant effect on stock prices in the company oil and gas sub-sector mining listed on the Indonesian stock exchange for the 2012-2017 period, the hypothesis is rejected, 3) Return on assets and net profit margins have a significant effect on stock prices in the oil and gas sub-sector mining companies listed on the Indonesian stock exchange for the 2012 period -2017, then the hypothesis is accepted